A pathway for nurses from work strain to anger: mediation of social intelligence - Hanife Tiryaki Sen; Emine Türkmen; Hilal Kuşcu Karatepe; Demet Yurtsever (BMC Health Services Research)
Abstract Background This study aimed to determine the mediating role of social intelligence in the effect of nurses’ work-related strain on trait anger and anger expressions. The challenging working conditions for nurses often result in increased strain and anger. Social intelligence could help to manage anger. Methods This cross-sectional, descriptive study was conducted with 446 nurses at a public hospital in Türkiye between April and May, 2021. The questionnaire consisted of socio demographics, Trait Anger and Anger Expression Inventory, Tromso Social Intelligent Scale, and Work-Related Strain Inventory. The data was collected face to face. Descriptive statistics and Pearson’s correlation coefficient were conducted using SPSS (v.26) and mediation analysis was conducted using PROCESS macro (Hayes, model 4). Findings Social intelligence played a mediating role in the effect of work-related strain on trait anger, anger-in, anger-out, and anger-control (β = 0.105, β = 0.100, β = 0.131, β=-0.136, respectively). Social intelligence reduced the effect of work-related strain on trait anger and anger in/out expressions, while increasing anger control. Conclusion The findings of this study show that social intelligence could be used to manage anger of nurses. Nurse managers could implement initiatives aimed at managing nurses’ anger and anger expressions through the decreasing of work-related strain and increasing of nurses’ social intelligence.